A laser system for cooling and trapping of fermionic potassium. - Wijaya, Yenny. (2010)
In this final year project, a laser system for cooling and trapping of fermionic potassium was realized. Two external cavity diode lasers (ECDLs) at 767 nm with a linewidth of 1 MHz were built for the cooling laser and repumping laser. Tapered amplifiers are used to amplify the power of both lasers in the master oscillator power amplifier (MOPA) configuration. The cooling laser is then frequency-stabilized to an atomic resonance with AC-locking on a saturation spectroscopy signal. The repumping laser is locked with respect to the cooling laser by using trombone locking that rely on the beat signal of both lasers. Acousto-optic modulators (AOMs) are used to shift the frequency of lasers for the various beams needed for the experiment: cooling beam, repumper beam, and imaging beam.